Proof of a Turnpike Theorem: The "No Joint Production" Case - Morishima, M. (Review of Economic Studies, 1961)
Journal Article Prices and the Turnpike: II. Proof of a Turnpike Theorem: The "No Joint Production" Case Get access M. Morishima M. Morishima Osaka, Japan Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 28, Issue 2, February 1961, Pages 89–97, https://doi.org/10.2307/2295706 Published: 01 February 1961